Fundamentals of Entrepreneurship (ENT300) : Business Planning Saaaa Sdn. Bhd. / Afiq Fakhrul Ismail … [et al.] - Ismail, Afiq Fakhrul; Abdul Halil, Muhammad Ariff Aiman; Mohamed Faruk, Amar Mohamed Fadhilah; Ahmad Hasbie, Shahrul Izzat; Sudin, Alma’ Ashsyahir (2019)
UiTM Campus Samarahan 2 consists a lot of student from a different background and a different perspective. Some of them has a problem and some are not. One of the common problem happened among the student are that they do not have a fast internet connection. This will affect their performance in any task related to research. We, SAAAA SDN. BHD., are fully ready to provide cyber cafe services to the student in this campus. The opportunity of doing this business is widely open because this campus has no cyber cafe company established yet. But we still have near competitors which is Anis Printing and Suria Printing located in this campus.